Impact of Pseudomonas aeruginosa carriage on intensive care unit-acquired pneumonia: a European multicentre prospective cohort study - Recanatini, C; van Werkhoven, C H; van der Schalk, T E; Paling, F; Hazard, D; Timbermont, L; Torrens, G; DiGiandomenico, A; Esser, M T; Wolkewitz, M; Sifakis, F; Goossens, H; et al. (Clinical microbiology and infection, 2025)
OBJECTIVES: Pseudomonas aeruginosa (PA) is a common causative pathogen of pneumonia acquired in the intensive care unit (ICU). The aim of this study was to determine the incidence of PA ICU pneumonia (PAIP) and to quantify its independent association with PA colonization at different body sites. METHODS: Adult patients on mechanical ventilation at ICU admission were prospectively enrolled across 30 European ICUs. PA colonization in the perianal area and in the lower respiratory tract was assessed within 72 hours after ICU admission and twice weekly until ICU discharge. PAIP development was evaluated daily. Competing risk models with colonization as a time-varying exposure and ICU death and discharge as competing events were fitted and adjusted for confounders to investigate the association between PA carriage and PAIP. RESULTS: A total of 1971 subjects were enrolled. The colonization prevalence with PA in the first 72 hours of ICU admission was 10.4% (179 perianal and 51 respiratory), whereas the acquisition incidence during the ICU stay was 7.0% (158 perianal and 47 respiratory). Of the 43 (1.8%) patients who developed PAIP, 11 (25.6%) were PA colonized on admission and 9 (20.9%) acquired colonization before PAIP onset. Both perianal (adjusted subdistribution hazard ratio, 4.4; 95% CI, 1.7-11.6) and respiratory colonization (adjusted subdistribution hazard ratio: 4.6, 95% CI, 1.9-11.1) were independently associated with PAIP development. DISCUSSION: PAIP incidence was higher in PA colonized vs. non-colonized patients. Colonization of both the rectum and of the respiratory tract was associated with development of PAIP. The increased risk of PA colonization for subsequent infection provides an opportunity for targeted preventive interventions.
Keywords: lidé; přenašečství; Middle Aged; Adult; prospektivní studie; Pseudomonas aeruginosa; Female; infekce spojené se zdravotní péčí; Prevalence; Evropa; Incidence; Pseudomonas Infections; jednotky intenzivní péče; Humans; Prospective Studies; lidé středního věku; Cross Infection; mužské pohlaví; ventilátorová pneumonie; Intensive Care Units; pseudomonádové infekce; ženské pohlaví; prevalence; Male; Aged; incidence; Pneumonia, Ventilator-Associated; Europe; Carrier State; dospělí; senioři